1993
DOI: 10.1083/jcb.121.5.977
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of the 68- and 72-kD proteins of signal recognition particle with 7S RNA.

Abstract: Abstract. Signal recognition particle (SRP), the cytoplasmic ribonucleoprotein particle that mediates the targeting of proteins to the ER, consists of a 7S RNA and six different proteins. The 68-(SRP68) and 72-(SRP72) kD proteins of SRP are bound to the 7S RNA of SRP as a heterodimeric complex (SRP68/72). Here we describe the primary structure of SRP72 and the assembly of SRP68, SRP72 and 7S RNA into a ribonucleoprotein particle.The amino acid sequence deduced from the cDNA of SRP72 reveals a basic protein of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 32 publications
4
43
1
Order By: Relevance
“…The SRP68͞SRP72 complex from the SRP also binds SRP RNA independently from the other SRP proteins, but the interaction is stabilized by SRP19 and͞or SRP54 binding (27). When in vitro expressed proteins are studied, SRP68 binds SRP RNA before SRP72, but its binding is stabilized by SRP72 binding (27,28). Our results here show that all three of these proteins visit the nucleolus and, therefore, can interact with SRP RNA.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The SRP68͞SRP72 complex from the SRP also binds SRP RNA independently from the other SRP proteins, but the interaction is stabilized by SRP19 and͞or SRP54 binding (27). When in vitro expressed proteins are studied, SRP68 binds SRP RNA before SRP72, but its binding is stabilized by SRP72 binding (27,28). Our results here show that all three of these proteins visit the nucleolus and, therefore, can interact with SRP RNA.…”
Section: Discussionmentioning
confidence: 61%
“…SRP19 protein is known to bind SRP RNA independently of other SRP proteins or factors (9,30). The SRP68͞SRP72 complex from the SRP also binds SRP RNA independently from the other SRP proteins, but the interaction is stabilized by SRP19 and͞or SRP54 binding (27). When in vitro expressed proteins are studied, SRP68 binds SRP RNA before SRP72, but its binding is stabilized by SRP72 binding (27,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposing canine SRP to high ionic strength conditions released SRP72 from the RNA as a stable heterodimer with SRP68 (Scoulica et al 1987). Early in vitro studies carried out in reticulocyte lysates suggested that SRP72 interacted with the RNA-bound SRP68 only through protein-protein interactions (Lütcke et al 1993). More recently, however, human SRP72 was shown to bind to the SRP RNA independently of SRP68 or any other SRP proteins via a 56 amino acid residue domain (Iakhiaeva et al 2005).…”
Section: Iakhiaeva Et Almentioning
confidence: 99%
“…These studies have demonstrated that the SRP9/SRP14 heterodimer is required for the inhibition of translation elongation and that the SRP68/SRP72 heterodimer is involved in the interaction of SRP with SRP receptor (Siegel and Walter, 1988a;Lutcke et al, 1993;Zopf et al, 1993;Hauser et al, 1995;Thomas et al, 1997). SRP54 is the most highly conserved component of SRP and comprises two distinct domains.…”
Section: Introductionmentioning
confidence: 99%